INTER-CIVILIZATIONAL CHALLENGES OF THE GLOBALIZED WORLD: LINGUO-SOCIAL ASPECT - Abysova, Mariia (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2023)
The article is devoted to the analysis of the sociolinguistic project "Word of the Year" as a mechanism for the formation of social knowledge. Regular data from monitoring studies of lexemes that denote phenomena and processes that are in the focus of public attention allow us to take them into account while forming strategic communication to overcome inter-civilizational challenges.